Analysis Of The Concept Of Human Equality And Gender In Religious Relations In A Multicultural Society - Pratama, M. Arifky; Suradi, A; Herawati, Emy; Irama, Dedi (Sekolah Tinggi Agama Islam (STAI) Bumi Silampari, 2024)
This study analyzes the concept of human and gender equality in religious relations within Indonesia's multicultural society. The main objective is to explore the perspectives of major religions in Indonesia, such as Islam, Christianity, Catholicism, Hinduism, Buddhism, and Confucianism, on human and gender equality, and how these teachings interact in a diverse cultural context. A descriptive qualitative approach using literature review was employed. The findings reveal that despite doctrinal differences, all religions share common values of human dignity, compassion, and social justice. Gender equality is recognized in each religious teaching, emphasizing the importance of equal treatment for both men and women. Additionally, the study underscores the need for more robust interfaith dialogues to reduce gender discrimination and foster a more inclusive and harmonious social environment. Collaboration across religious communities can strengthen these equality values, contributing to more equitable social and economic development in Indonesia. This cooperative effort is essential for promoting peace and cohesion in a society rich with cultural and religious diversity.